Role of stimulated by retinoic acid 6 in 46 children of coarctation of the aorta - Xin Jin; Zhengxia Pan; Zhenjiang Zhao; Da Ouyang; Jinjie Qin; Jie Tian (Heliyon)
(1) ObjectiveCoarctation of the aorta (CoA) is a complex congenital heart disease. Research on differential genes in patients with CoA and other groups of aortas and investigating the pathogenesis of aorta coarctation is essential for prevention and diagnosis. (2) Methods: This study was conducted between January 2019 and December 2021. The first step was the analysis of differential genes in four groups of aortic tissues. Group A: 46 cases, coarctation specimen of the CoA group; Group B: 46 cases, anastomotic margin specimen of the CoA group; Group C: 22 cases, aortic specimen of the aortic stenosis group; and Group D: 6 cases, aorta of the necropsy group. Genomic and proteomic differences were compared in aortic specimens from different patient groups in Southwestern China. The second step the CRISPR technology was used to knock out the differential genes in mice. The phenotypes were verified using ultrasound after obtaining homozygous mice. (3) Results: Quantitative polymerase chain reaction indicated that BMP4, Smad4, STRA6, CRABP I, and COX-2 genes were statistically downregulated in group A than in other groups. STRA6 expression was 0.33 ± 0.66 in group A and 1.03 ± 0.20 in group D. The difference between the two groups was statistically significant. Western blotting revealed that BMP4, Smad4, STRA6, and CRABP I had a low expression in group A at the proteomic level. STRA6 protein was 0.13 ± 0.02 in group A and 0.48 ± 0.07 in group D. Group A decreased by 73.7 %, a statistically significant difference. Double-labeled immunofluorescence demonstrated co-expression of BMP4 and STRA6 in the tunica adventitia vasorum of group A. However, BMP4 expression in the tunica adventitia vasorum and endangium of the constricted aorta showed a double-loop sign. Primary filial generation offspring were generated using CRISPR knockout of the STRA6 gene. The first filial generation was mated with the wild-type mice to produce the second filial generation. 72.7 % homozygous mice in the fourth week of the second filial generation were detected using ultrasound, indicating a reduction in aortic diameter. (4) Conclusions: BMP4, STRA6, and COX-2 genes may be associated with CoA in Southwestern Chinese patients. STRA6 knockout, a gene that initiates the retinoic acid pathway, may lead to CoA.